"Nonsignificant" early repolarization pattern on postresuscitation ECG as a harbinger of impending electrical storm. Issue 3 (9th September 2019) - Takasugi, Nobuhiro; Kubota, Tomoki; Okura, Hiroyuki
Abstract: We report a 55‐year‐old man who was resuscitated from out‐of‐hospital cardiac arrest and subsequently developed three episodes of ventricular fibrillation (VF) on the same day. Early repolarization (ER) pattern was not significant (<0.1 mV) on postresuscitation ECG. However, ER pattern became evident (0.25 mV) before the onset of VF and then completely disappeared. The unusual dynamics of ER pattern observed in the present case could be called "masked" ER syndrome.